Biogas upgrading via CO2 absorption using monosodium glutamate-promoted potassium carbonate in packed absorption column: Design and performance assessment - Bambang Trisakti; Rivaldi Sidabutar; Irvan; Hani Suhastifa Rambe; Vikram Alexander; Andrew Moses Noverindo Simanjuntak; Joshua Syaloom Silalahi; Rafael Aginta Sitepu; Michael Michael; Juan Akmal Nasution; Yasmin Nabilah; Hiroyuki Daimon (South African Journal of Chemical Engineering)
Biogas, an alternative energy source derived from organic materials, particularly POME, is produced through anaerobic digestion. The utilization of an UASB-HCPB fermenter has successfully yielded biogas with elevated methane content. However, the produced biogas still contained a moderate amount of CO2, necessitating further purification to make the biogas suitable for engine fuel applications. The presence of CO2 must be mitigated through an absorption method. The amount of CO₂ removed from biogas required an absorption system designed to utilize environmentally friendly solvents that can operate effectively at low pressures. The absorption design is important in designing absorber columns, particularly packed column types. It requires careful consideration of flow rates and absorbent concentrations to ensure optimal performance and suitability for industrial applications. This study aims to elaborate the design, fabrication, and performance of a packed absorption column for CO2 removal utilizing K2CO3 as a solvent with MSG as a promoter. K2CO3 promoted with MSG represents an eco-friendly solvent with potential for biogas purification applications. The novelty of this study highlights a gap in integrating biogas production and purification design, wherein biogas generated from anaerobic digestion of POME undergoes purification via an absorption system. Experimental parameters included absorbent flow rates of 1, 1.5, and 2 L/min; a biogas flow rate of 20 L/min; promoter concentrations of 1, 3, and 5 %; temperatures of 35, 45, and 55 °C; and a contact time of 5 min. Results indicated that optimal CO2 removal (47.38±1.58 %) was achieved with an absorbent flow rate of 2 L/min and MSG concentration of 5 %. Based on the calibration results, the distilled water, air, and CO2 flowmeters have regression values (R²) of 0.9947, 1.0000, and 0.9253, respectively. The highest CO2 removal was 94.44 % on CO2 flow rate of 5 L/min, air flow rate of 20 L/min and absorbent flowrate of 1.8 L/min. Maximum CO2 loading (0.0081 mol CO2/mol K2CO3) was obtained at an absorbent flow rate of 1 L/min and MSG concentration of 5 %. Temperature effects revealed optimal CO2 removal (63.32±0.42 %) at 55 °C, while peak CO2 loading (0.00987 mol CO2/mol K2CO3) occurred at 45 °C. At 55 °C, the final biogas composition achieved was 94.18 % CH4, 5.81 % CO2, and 0.01 % H2S. These results indicate an increase in the effectiveness of CO2 removal and high-purity biogas products. However, future research of synergistic study is needed on the regeneration capability of monosodium glutamate-activated K2CO3 for long-term CO2 absorption. Futhermore, development of the absorption column design is also needed by considering the operating pressure. It is expected that this initial study on integrated biogas production and purification can be further developed and applied to the palm oil industry to support the implementation of sustainable zero waste technology.